2019
DOI: 10.1123/ijsnem.2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Body Composition Adaptations in Elite White and Polynesian Rugby Union Athletes

Abstract: During preseason training, rugby union (RU) athletes endeavor to enhance physical performance characteristics that are aligned with on-field success. Specific physique traits are associated with performance; therefore body composition assessment is routinely undertaken in elite environments. This study aimed to quantify preseason physique changes in elite RU athletes with unique morphology and divergent ethnicity. Twenty-two White and Polynesian professional RU athletes received dual-energy X-ray absorptiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 28 publications
7
26
2
Order By: Relevance
“…These findings support previous studies which demonstrated forwards as having different body composition [ 11 , 12 , 13 , 15 , 16 ] and anthropometric characteristics than backs, including greater strength and absolute power measures, but slower sprint performance and less aerobic fitness [ 6 , 7 , 10 , 33 ]. The characteristic differences between forwards and backs can be attributed to specific positional demands, in which being larger and stronger can assist forwards with winning line outs, scrumming with more force [ 34 ], gaining and retaining possession of the ball at break downs [ 6 ], and absorbing more collisions through tackles and ball carries [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings support previous studies which demonstrated forwards as having different body composition [ 11 , 12 , 13 , 15 , 16 ] and anthropometric characteristics than backs, including greater strength and absolute power measures, but slower sprint performance and less aerobic fitness [ 6 , 7 , 10 , 33 ]. The characteristic differences between forwards and backs can be attributed to specific positional demands, in which being larger and stronger can assist forwards with winning line outs, scrumming with more force [ 34 ], gaining and retaining possession of the ball at break downs [ 6 ], and absorbing more collisions through tackles and ball carries [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Players all possess varying levels of physical characteristics, such as anthropometric (height, body mass, skinfold) and body composition (lean mass, fat mass, bone mass) in order to achieve adequate levels of the desired aforementioned fitness qualities and to meet specific positional demands of the sport [ 7 , 8 , 9 ]. Numerous studies have shown that these fitness [ 5 , 7 , 10 ] and physical characteristics [ 11 , 12 , 13 , 14 , 15 , 16 ] vary greatly depending on the player’s position within the team. In general, forwards have a greater body mass and strength emphasis in order to scrummage with more force, tolerate more collisions and gain and retain possession of the ball [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…week period [24]. Furthermore, these findings are similar to those reported for bone mineral density, in that same-day precision underestimated true variability, which could potentially result in an incorrect interpretation of longitudinal change [25].…”
Section: Discussionsupporting
confidence: 80%